Understanding social identities through the ceramic evidence: the case of the “Quartiere degli Artigiani” in Calvatone-Bedriacum - E. Intagliata, Emanuele (Rei Cretariae Romanae Fautorum Acta, 2015)
The site of Bedriacum is located in the modern municipality of Calvatone, between the cities of Mantova and Cremona, in the province known as Cisalpine Gaul in Roman times. It owed its existence to its strategic position along the via Postumia, the road constructed by Spurius Postumius Albinus in AD 148 stretching through the Po Valley, and enjoyed a good level of prosperity as a crossing point of the river Oglio.